Optimizing the muscular training through alternated contraction regimes at junior female players I - Vladu, L. (Journal of Physical Education and Sport, 2010)
The research purpose: is that of bettering the muscular training during the preparation process of the female junior I volleyball players, adapted to the game tasks, through elaborating and confirmation of the alternate contraction regimes programs, thus ensuring an optimal and rationalized training, with the purpose of reaching the proposed performance objectives. The research hypothesis: by using the alternated contraction regimes to adapt the muscular training to the players` posts and morpho-functional particularities, we consider that we may determine the increase of the players` performance abilities. Investigation methods: analysis and generalization of the special field of interest data, the measurements and tests method, the pedagogical experiment and the statistic-mathematical method. Applied test trials: - Throwing the medicinal ball (3kg); - Abdomen exercises; - Press genuflexions (1RM); - Chest push-ups from a laid position (1RM).